NYAMPLUNG SEED OIL RESIN SEPARATION - Alima Amalia, Hiskia
Nyamplung plants have the capacity to generate biofuel from oil. However, nyamplung seed oil cannot be used directly. This is due to the presence of contaminants, including resin, that can lower the quality of nyamplung seed oil. In order not to become waste, resin needs to be utilized. Therefore, research is needed on the separation of nyamplung seed oil resin to identify the resin content and type of nyamplung seed resin so that its benefits can be determined. In this study, mechanical and liquid-liquid extraction techniques were used to extract a mixture of resin and nyamplung seed oil. This study aimed to classify and identify the resin found in nyamplung seed oil. This study's objectives are to evaluate the resin yield from nyamplung seeds, identify the terpenoid chemicals found in the resin of nyamplung seed oil, and identify the resin groups and categorization. This study is divided into five primary stages: raw material preparation, nyamplung seed pressing, mixture separation, fractional purification, and resin analysis. A 1.25:1 ratio of ethanol to n-hexane solvents was used for the mixture's separation. Subsequently, ethanol was added in a 1:1 ratio to the purified oil fraction. N-hexane was added at a 1:1 ratio during the resin fraction's purification process. Based on the analysis, the terpenoids contained in the nyamplung seed oil resin contained morusin dimethyl ether, squalene, and 1-Phenanthrenecarboxylic acid compounds, 1,2,3,4,4a,4b,5,9,10,10a-decahydro-1,4a-dimethyl-7-(1-methylethyl)-, methyl ester, [1R-(1?,4a?,4b?,10a?)]-. The three main types and groupings of resin found in nyamplung seed oil are triterpenoids, diterpenoids, and monoterpenoids. With two solvents for each bait, the resin yield of nyamplung seeds was 13% and 16% of the nyamplung seed extract. 24.55 grams of double resin from 190.84 grams and 31.06 grams from 182.61 grams of nyamplung seed extract made up the total weight of each bait.